Development and biological evaluation of nanoencapsulated-based pyrethroids with synergists for resistance management of two soybean pests: insights for new insecticide formulations - Boff, Jéssica S.; Reis, Alexandre C.; de Oliveira, Jhones L. [UNESP]; Gross, Renata B.; Fraceto, Leonardo F. [UNESP]; Melo, Adriano A.; Bernardi, Oderlei (Wiley, 2023)
Background: Chemical control is commonly used against Euschistus heros (F.) and Chrysodeixis includens (Walker) in soybean fields in South America. However, previous studies reported that these pests have reduced susceptibility to pyrethroids in Brazil. On this basis, we developed and evaluated nanoencapsulated-based bifenthrin (BFT) and λ-cyhalothrin (LAM) with the synergists piperonyl butoxide (PBO) and diethyl maleate (DEM) for insect resistance management (IRM). Results: Nanoformulations of BFT and LAM with PBO and DEM presented good physical–chemical characteristics and were stable. The spherical morphology of all systems and the encapsulation efficiency in nanostructured lipid carriers did not change when synergists were added. Nanoencapsulated BFT with DEM applied topically increased the susceptibility of E. heros to BFT by 3.50-fold. Similarly, nanoencapsulated BFT and LAM with PBO in diet-overlay bioassays increased the susceptibility of C. includens to both chemicals by up to 2.16-fold. Nanoencapsulated BFT and LAM with synergists also improve control efficacy of both species, causing higher mortality than commercial products containing these chemistries. Conclusions: It is possible to develop nanoencapsulated-based formulations of BFT and LAM with PBO or DEM, and these nanoformulations have the potential to improve control of E. heros and C. includens with recognized low susceptibility to pyrethroids. This study provides updates for designing new insecticide formulations for IRM. © 2022 Society of Chemical Industry.
Keywords: nanoformulation; neotropical brown stink bug; sodium channel modulators; soybean looper